Classified Region Algorithm for Fast Intermode Decision in H.264/AVC Encoder. (13th September 2010) - Bharanitharan Bharanitharan, K. K.; Liu Liu, Bin-Da Bin-Da; Yang Yang, Jar-Ferr Jar-Ferr
Abstract : H.264, MPEG-4 Part 10, is the latest digital video coding standard that achieves very high data compression by using several new coding features. One of the new features is variable block sizes for interframe coding to increase compression efficiency. However, to achieve this, the H.264 encoder employs a complex mode decision technique based on rate-distortion optimization (RDO) that requires high computational complexity, which significantly increases the encoder complexity. In this paper, we propose a classified region algorithm (CRA) that analyzes the spatial and temporal homogeneity of the block by using cross differences to reduce the number of modes that are required for RDO calculation in inter mode decision. The proposed low computational complexity algorithm significantly reduces the number of inter modes without affecting the video quality. The experimental results show that the proposed method is able to reduce complexity by up to 67% on average with negligible degradation in both objective and subjective quality.